Pengetahuan dan Sikap Remaja terhadap Kekerasan Seksual - Yamin, Ahmad; Ulpa, Maria; Kurniawan, Kurniawan; Mulya, Adelse Prima (Journal of Telenursing (JOTING), 2024)
This study aims to analyze the relationship between knowledge and adolescents' attitudes towards sexual violence. The research method uses a correlational approach, with a sample size of 98 adolescents selected through proportional stratified random sampling. Data were analyzed using Pearson correlation. The results show that 40.8% of students have poor knowledge, 37.8% have good knowledge, and 21.4% have adequate knowledge. In terms of attitudes towards sexual violence, 57.1% of adolescents have a positive attitude, while 42.9% have a negative attitude. The Pearson correlation test results showed a p-value of 0.147. The conclusion is that there is no relationship between knowledge and adolescents' attitudes towards sexual violence, but efforts to improve attitudes and personal boundaries among students are necessary, as nearly half have a negative attitude. Keywords: Sexual Violence, Knowledge, Adolescents, Attitudes